2018
DOI: 10.1155/2018/4956079
|View full text |Cite
|
Sign up to set email alerts
|

Capybara Oil Improves Hepatic Mitochondrial Dysfunction, Steatosis, and Inflammation in a Murine Model of Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is recognized as the most common cause of liver dysfunction worldwide and is commonly associated with obesity. Evidences suggest that NAFLD might be a mitochondrial disease, which contributes to the hepatic steatosis, oxidative stress, cytokine release, and cell death. Capybara oil (CO) is a rich source of polyunsaturated fatty acids (PUFA), which is known to improve inflammation and oxidative stress. In order to determine the effects of CO on NAFLD, C57Bl/6 mice were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…In the present study, the BM of mice fed with a high-fat diet increased in relation to animals fed with a control diet. Data corroborate the literature, in which we found several works that relate the administration of a high-fat diet with the increase in BM in mice [ 25 , 37 ]. Furthermore, this type of diet has already been seen to develop consequences such as obesity, hyperinsulinemia, hyperglycemia, hypertension, and liver damage [ 26 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, the BM of mice fed with a high-fat diet increased in relation to animals fed with a control diet. Data corroborate the literature, in which we found several works that relate the administration of a high-fat diet with the increase in BM in mice [ 25 , 37 ]. Furthermore, this type of diet has already been seen to develop consequences such as obesity, hyperinsulinemia, hyperglycemia, hypertension, and liver damage [ 26 , 38 ].…”
Section: Discussionsupporting
confidence: 91%
“…Terefore, the search for an alternative source of these AGs is essential, and it is in this scenario that capybara oil presents itself. Tree studies have already shown the benefts that this capybara-derived by-product can generate, including accelerating the healing process in rat skin wounds; improving steatosis, infammation, and hepatic mitochondrial activity; and improving pathophysiology and kidney infammation [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALT levels in the plasma are used as a marker to indicate hepatic disorders. In fact, Marinho et al [55] showed that capybara oil decreased plasma ALT levels and improved hepatic steatosis. Moreover, an n-3 PUFA-enriched diet decreased serum ALT levels and damaged areas of the liver, including hepatocyte necrosis, in a Con-A-induced hepatitis mouse model [56].…”
Section: Effects Of 8-hepe Extracted From E Pacifica On Nafldmentioning
confidence: 99%
“…In addition, the oil is also made up of oleic (35.6 to 39.8%) and palmitic (20.7 to 24.3%) PUFAs [19]. There are still few studies using CO, but data in the literature shows that it is able to accelerate the healing process in skin wounds in mice [20] and improve steatosis, inflammation and mitochondrial activity liver [21].…”
Section: Introductionmentioning
confidence: 99%